2020
DOI: 10.1093/ckj/sfaa088
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects of severe acute respiratory syndrome coronavirus 2 on the kidney in coronavirus disease patients

Abstract: Among patients hospitalized for novel coronavirus disease (COVID-19), between 10 and 14% develop an acute kidney injury and around half display marked proteinuria and haematuria. Post-mortem analyses of COVID-19 kidney tissue suggest that renal tubular cells and podocytes are affected. Here we report two cases of collapsing glomerulopathy and tubulointerstitial lesions in living COVID-19 patients. Despite our use of sensitive reverse transcription polymerase chain reaction techniques in this study, we failed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 23 publications
2
40
0
6
Order By: Relevance
“…The first histological analysis of post-mortem renal biopsies of 26 patients from China showed acute tubular injury, collapsing glomerulopathy, vascular injury and podocyte foot process effacement [4]. Four subsequent case reports (Table 1) in which patient presented with AKI, all reported ATI/ATN and CG [5][6][7][8]. Our case report describes a rare presenting complaint of COVID-19 patients with kidney involvementthat of new-onset nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The first histological analysis of post-mortem renal biopsies of 26 patients from China showed acute tubular injury, collapsing glomerulopathy, vascular injury and podocyte foot process effacement [4]. Four subsequent case reports (Table 1) in which patient presented with AKI, all reported ATI/ATN and CG [5][6][7][8]. Our case report describes a rare presenting complaint of COVID-19 patients with kidney involvementthat of new-onset nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 70%
“…Our case report describes a rare presenting complaint of COVID-19 patients with kidney involvementthat of new-onset nephrotic syndrome. Interestingly, the Asian-Indian patient (case 1) presented initially with minimal changetype glomerulopathy which progressed to CG with time, hinting at the possibility that non-AA and/or asymptomatic COVID-19 patients may pass through a more benign glomerular phase (as pointed out by Couturier et al [8]) before developing florid CG, while genetic predisposition [6] like APOL-1 positivity coupled with symptomatic COVID-19 may push patients of African-American ethnicity to develop more severe glomerular pathology (that of CG) from the outset ( Table 1). The exact mechanism of podocyte injury in COVID-19 infection is still unknown, although several hypotheses have been put forward.…”
Section: Discussionmentioning
confidence: 92%
“…In this journal, Couturier et al [ 18 ] recently reported on the clinical course and pathology findings for two COVID-19 patients with collapsing focal segmental glomerulosclerosis (FSGS) and severe tubulointerstitial lesions. This specific subtype of glomerulonephritis is often observed in patients affected by the human immunodeficiency virus (HIV) [ 19 ].…”
Section: Covid-19 and Acute Kidney Injurymentioning
confidence: 99%
“…Both patients were submitted to kidney biopsy during the course of their disease because of progressively increasing proteinuria and worsening of kidney function concurrently with the worsening of lung disease and hypoxia [ 18 ]. In order to better characterize the role of SARS-CoV-2 in the development of collapsing FSGS, the authors performed reverse transcription polymerase chain reaction (RT-PCR) assay on the renal tissue specimen of one of the two patients without detecting any molecular expression of the virus.…”
Section: Covid-19 and Acute Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation